The role of painting in forming reality (Damascus University Journal for engineering sciences, 2021)
The way which  we see things differs after each aesthetic experience  we live, and sometimes a work of art affects the way we see our physical surroundings, and the way we read people, situations and events, even in the smallest details of our life. Everything that humans created was created first in the form of an idea and then embodied in reality, so if we are interested in what is happening in our external world, we have to be interested in what is happening in the inner  world. What happens within our thoughts and feelings and in our imaginations, those images that rush in the imagination, may be tools and means that enable us to make that change that  we want in the reality.Here, the role of art and its impact on the life of the individual appears, as it is the bridge between the invisible world that is abuzz within the human being and the visible world that we call the physical reality, and this research did not come to confirm this role, but rather came to study this influence, and to ask the most important question: Is it possible to control This effect? This research has adopted the descriptive and analytical approach in studying the effect of the painting on reality and analyzing results to answer the question raised in the research.
Keywords: Painting; forming reality